26.6k views
4 votes
10b-25-3b=4b-1 show work help

User Lula
by
6.0k points

2 Answers

4 votes
What ypu need to do here is just isolate b:
So first you have to move like terms to the same side of the equation and combine them.

In order to do that , you can add 25 to both sides of the equation to move 25 to the other side:
10b -3b -25 +25 = 4b -1 +25
10b -3b = 4b + 24

Then subtract 4b in both sides of the equation:
10b -3b -4b =24

Now just combine like terms :
3b = 24

And divide both sides of the equatoon by 3
3/3b = 24/3
b = 8
Thats the awnser : b = 8
I hope you understood my brief explanation
User David Hellsing
by
5.2k points
2 votes
b = 8

10b - 25 - 3b = 4b - 1

10b - 3b - 25 = 4b - 1 (Arrange like terms)

7b - 25 = 4b - 1 (Combine like terms)

7b - 4b = 25 - 1 (Arrange like terms again)

3b = 24 (Combine like terms again)

3b ÷ 3 = 24 ÷ 3 (Isolate the variable)

b = 8
User Nishanth Shaan
by
6.5k points